Succeed the Sandler way 14 personal and professional breakthroughs - Scheible, Karl (Gildan Audio, 2019)
Succeed The Sandler Way features fourteen compelling success stories from real people who have used the Sandler Selling System to create major personal and professional breakthroughs. Each chapter is an in-depth profile of an actual Sandler client. As each case study proves, the guiding principle for creating a breakthrough is deceptively simple-sounding: Be candid with yourself. Taking a good, hard look at yourself is a prerequisite of any breakthrough.
Downloadable audio file
Keywords: Business; Affaires; BUSINESS & ECONOMICS; General; Downloadable audio books; Audiobooks; Livres audio